PENGARUH REPUTASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN BENGKEL YAMAHA FLAGSHIP SHOP SEMARANG (Students' Journal of Economic and Management, 2014)
This study is a study that examines the effect of Reputation and Influence Satisfaction and Quality Services To Impact On Customer Loyalty . Research conducted on the Yamaha customers Flagship Shop Semarang. a sample of respondents in this study were 100 respondents . The results showed that , the first hypothesis there is a positive effect on customer satisfaction workshop Reputation Yamaha Flagship shop in Semarang , the second hypothesis there is a positive effect on customer loyalty workshop Reputation Yamaha Flagship Shop Semarang , the third hypothesis there is a positive effect of Service Quality on Customer Satisfaction workshop Yamaha Flagship Shop Semarang , the fourth hypothesis there is a positive effect of Service Quality on customer Loyalty workshop Yamaha Flagship Shop Semarang , the fifth hypothesis there is a positive effect of satisfaction on customer loyalty workshop Yamaha Flagship Shop Semarang . Keywords : Reputation , Service Quality , Satisfaction and Loyalty